A comparative study of well-being, resilience, mindfulness, negative emotions, stress, and burnout among nurses after an online mind–body based intervention during the first COVID-19 pandemic crisis - Cepeda-Lopez, Ana Carla; Solís Domínguez, Leticia; Villarreal Zambrano, Sofía; Garza-Rodriguez, Iris Y.; del Valle, Alejandra Cortes; Quiroga-Garza, Angélica (Frontiers in Psychology, 2023)
Background To mitigate against the possible adverse effects of stress among nurses due to the COVID-19 outbreak, we designed a 12-week mind–body based online intervention program to promote well-being and prevent stress-related disorders such as burnout. Our study aimed to compare the impact of the intervention on perception of stress, negative emotions, burnout, mindfulness, resilience, and well-being at pretest and 6 months post-intervention and to compare the effect among nurses working at two different hospitals. Methods We conducted an uncontrolled trial using a convenience sample of nurses working at two hospitals in Mexico: one designated to treat confirmed COVID-19 patients (COVID-hospital) and the other whose patients had a negative COVID-19 test on admission (Non COVID-hospital). The 12 week online intervention consisted of 36 mind–body based micropractices, with subjective well-being as the primary outcome. Secondary outcomes were health perception, resilience, mindfulness, negative emotions, stress, and burnout. Results A pretest survey was completed by 643 nurses. Of the remaining valid responses, 82% were women, with a mean age of 34.8 (SD = 8.95) years old. For the analysis two groups of nurses were sampled by cluster: a COVID-hospital group of 429 (67%) nurses, and a non-COVID Hospital group of 214 (33%) nurses. The proportion lost to follow-up was 71% at postest (n = 188) and 42% at 6 months follow-up (n = 371). At pretest, non-COVID hospital nurses had lower subjective well-being and higher burnout than their COVID hospital counterparts. At postest, non-COVID hospital nurses displayed more negative emotions than their COVID hospital peers. At 6 months post-intervention, nurses experienced improved mindfulness, reduced negative emotions and stress, but a decrease in subjective well-being and resilience. Nurses working at the non-COVID hospital had significantly higher mean scores for burnout than those working at the COVID hospital. Conclusion The results of our study suggest that our online mind–body interventions can help to reduce stress and negative emotions, yet the effects on subjective well-being and resilience are uncertain. Further research is needed to gain a better understanding of their potential mechanisms and the associated efforts of such online interventions. Clinical Trial Registration ClinicalTrials.gov, NCT05515172.